Physical Inactivity Is Correlated with Levels of Quantitative C-reactive Protein in Serum, Independent of Obesity: Results of the National Surveillance of Risk Factors of Non-communicable Diseases in Iran (Journal of Health, Population and Nutrition, 2012)
Increased C-reactive protein (CRP) levels are associated with coronary heart disease, stroke, and mortality. Physical activity prevents cardiovascular disorders, which can be partly mediated through reducing inflammation, including serum CRP levels. The association of different intensities of physical activity, sedentary behaviours, and C-reactive protein (CRP) levels in serum was examined after adjustment for markers of adiposity, including waist-circumference and body mass index (BMI), in a large population-based study. Using data of the SuRFNCD-2007 study, a large national representative population-based study in Iran, the relationship between quantitative CRP concentrations in serum and physical activity was examined in a sample of 3,001 Iranian adults. The global physical activity questionnaire (GPAQ) was used for evaluating the duration and intensity of physical activity. Total physical activity (TPA) was calculated using metabolic equivalents for the intensity of physical activity. Quantitative CRP concentrations in serum were measured     with high-sensitivity enzyme immunoassay. The CRP levels in serum significantly correlated with TPA (r=-0.103, p=0.021 in men and r=-0.114, p=0.017 in women), duration of vigorous-intensity activity     (r=-0.122, p=0.019 in men and r=-0.109, p=0.026 in women), duration of moderate-intensity activity (r=-0.107, p=0.031 in men and r=-0.118, p=0.020 in women), and duration of sedentary behaviours (r=0.092,     p=0.029 in men and r=0.101, p=0.022 in women) after multiple adjustments for age, area of residence, BMI, waist-circumference, smoking, and diabetes mellitus. Physical activity (of both moderate and vigorous intensity) is inversely associated with the quantitative CRP levels in serum, independent of diabetes and body adiposity.   DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11278   J HEALTH POPUL NUTR 2012 Mar;30(1):66-72